L’apport de l’autoconfrontation collective interprofessionnelle à la santé au travail : le cas d’une clinique de l’activité en milieu scolaire - Emmanuel Poirel; Patricia Dionne; Simon Viviers (Activités)
The mental health of school professionals is at risk. By reducing the quality of workspaces, the pursuit of effectiveness, efficiency and economy would seem to be part of the problem. Within the framework of a research-intervention on occupational health, we introduced an activity clinic to address this problem. In this article, we present the work of a school committee responsible for workplace health and describe the processes mobilized during a collective interprofessional self-confrontation. The results show that the intervention improved the relationship between staff and the hierarchical superior, and mobilized the health committee around a project that enhanced individual and collective power to act.